May You Be Shot with Greasy Bullets: Curse Utterances in Turkish - Osam, Ülker Vancı (Nanzan University, Anthropological Institute, 1998)
Curse utterances are a remarkable linguistic form. While some languages have few curse utterances, other languages, such as Turkish, are well known for their imaginative and numerous curse expressions. This study surveys the characteristics and functions of curse utterances in Turkish by examining specific examples with concepts from speech act theory and ethnography of communication. Throughout the study the examples will help to demonstrate that curse utterances are more than linguistic routines, as they allow their "addressors" to enjoy a high degree of creativity and verbal flexibility within rather strict morphological and syntactical rules.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.2307/1178997) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: shot; utterances; curse; turkish